SAT0384 Multireader Reliability Using Us in Salivary Glands: An International Web Exercice to Evaluate a New Us Scoring (NUSC) in Primary Sjogren Syndrome. (9th June 2015) - Jousse, S.; Nowak, E.; Theander, E.; Hocevar, A.; Jonsson, M.; Milic, V.; Visink, A.; Saraux, A.; Bowman, S.J.; Devauchelle-Pensec, V.; Rout, J.; Brown, J.; et al.
Abstract : Background: Ultrasonography (US) has been shown to be a sensitive tool to diagnose major salivary gland echotexture abnormalities in primary Sjögren's syndrome (pSS). Objectives: The purpose of this study was [1] to assess definitions of the different ultrasonographic components of the salivary glands and [2] to study the reliability of these definitions on static images with an international web exercice. Methods: [1]The consensus exercice about definitions was done and discussed between 12 experts on the field of US pSS during 3 annual meetings. All experts were part of the US-pSS study group. [2]Using these preliminary definitions, a reliability exercice was done on static images. A centre (Brest- France) was in charge to send to the participants different representative US images collection of the agreed elementary lesions.30 parotid glands images and 30 submandibular glands images were sent to the experts by mail.They were asked to score each components of each glands in standardized file. Two rounds of exercicewere performed in order to obtain intra and inter reliability. The first round was in January 2014 and the second round was in March 2014. Inter and intra-observer agreements were estimated using the kappa index considering binary variables (agreements are almost perfect k:0.81 to 1.0; substantial: 0.61 to 0.8, moderate: 0.41 to 0.6, fair: 0.21 to 0.4, poor: -1.0 to 0.2). Results: All experts were trained for US of salivary gland with at least 5 years of experience. We obtained definitions about 8 different components evaluating the abnormal parenchyma (echogenicity, homogenicity, presence or absence of hyperechoic bands, number of hypoechoic ares, and location of hypoechoic areas, lymph nodes, presence or absence of calcifications, visualisation of posterior border) on salivary glands in pSS patients. Results of the reliability web exercise is shown on table 1. Without practical training session, we showed good results concerning the intra and inter observer reliabilities applying these definitions on US parotid gland and submandibular glands, particularly in taking homogeneity as the main important item in this definition. Reliabilities for calcifications and posterior band were low. Conclusions: This is the first consensus-based US definitions on salivary glands and its elementary components. These first results of the reliability exercice on static images without any training showed good results and permit to apply these preliminary definitions in routine practice and for further studies on pSS patients. Disclosure of Interest: None declared